FACTORS INFLUENCING THE ACADEMIC PERFORMANCE OF STUDENTS IN THE FACULTY OF TECHNICAL EDUCATION AT RAJAMANGALA UNIVERSITY OF TECHNOLOGY KRUNGTHEP - Jairtalawanich, Suwimol (Journal of Social Science and Cultural, 2024)
This research is a quantitative research that aims to study factors in learning and compare the academic achievement of students in the Faculty of Technical Education at Rajamangala University of Technology Krungthep. Classified according to general information of students and to study factors that influence students' academic achievement by using a questionnaire that contains general information and the actual current state of factors related to academic achievement and analyze statistical results. Consists of percentage, mean, and standard deviation. Test with t-statistic (T-Test), test with F-statistic (F-Test) and one-way analysis of variance (One-Way ANOVA) with student samples obtained from stratified sampling 124 students in years 1 to 4. The results of the study found that the factors that cause a significant difference at the 0.05 level (95% confidence) are residence and location of the original educational institution. This may be due to the residence of students from other provinces without parents to take care of them closely. Causing an impact on the academic achievement of students in the Faculty of Technical Education Rajamangala University of Technology Krungthep. And made it known that the factor that influences students' academic achievement is working to earn extra income and location of the original educational institution had the most influence, followed by year of study and education of parents There are 4 independent variables that have a linear relationship with students' academic achievement. This group of independent variables has a relationship with academic achievement of 91.2 percent and can explain academic achievement of 82.6 percent.